The Oxford handbook of management in emerging markets - Grosse, Robert E.; Meyer, Klaus, 1964- (New York : Oxford University Press, 2018)
Emerging Markets are the primary source of growth for business in the 21st century. This makes an understanding of managing businesses in emerging markets a fundamental building block for competing in today's global economy. This book's approach is to identify key elements of the business systems and competition in emerging markets around the world, and then to look at competitive strategies of local and multinational companies going into and coming out of these countries. Specific focus is offered on a selection of countries/regions.
Introduction to Managing in Emerging Markets / Klaus E. Meyer, Robert Grosse -- Consumer Behavior in Emerging Markets / t Operating Across Levels in the Global Economic Hierarchy: Insights from South Africa's Setting in Wider Africa and the World / Helena Barnard, Theresa Onaji-Benson -- Management in Southeast Asia: A Business Systems Perspective / Michael A. Witt -- Human Rights, Emerging Markets, and International Business / Florian Wettstein -- Economics, Transitions, and Traps in Emerging Markets / John M. Luiz -- Institutional Theory Perspectives on Emerging Markets / Tatiana Kostova, Valentina Marano -- Emerging Markets and the International Investment Law and Policy Regime / Karl P. Sauvant -- Financial Decisions, Behavioral Biases, and Governance in Emerging Markets / Emir Hrnjic, David M. Reeb, Bernard Yeung -- Comparative Corporate Governance in Emerging Markets / Ruth V. Aguilera, Ilir Haxhi.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on February 5, 2019).
Keywords: Management -- Developing countries; Marketing -- Developing countries -- Management; Small business -- Developing countries -- Management